2021
DOI: 10.3389/fimmu.2021.739675
|View full text |Cite
|
Sign up to set email alerts
|

Differential DNA Damage Response of Peripheral Blood Lymphocyte Populations

Abstract: DNA damage occurs constantly in every cell triggered by endogenous processes of replication and metabolism, and external influences such as ionizing radiation and intercalating chemicals. Large sets of proteins are involved in sensing, stabilizing and repairing this damage including control of cell cycle and proliferation. Some of these factors are phosphorylated upon activation and can be used as biomarkers of DNA damage response (DDR) by flow and mass cytometry. Differential survival rates of lymphocyte subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 50 publications
1
1
0
Order By: Relevance
“…Interestingly, we observed a significant increase in all DSB repair mechanisms after the first 2 Gy dose and a recovery to steady state at D8. This confirmed that the DDR can be stimulated after a physical insult in PBMCs and PBMCs recovered from this damage in few days [ 31 ]. Age does not have any effect on the DNA repair profiles, whether NHEJ, Syn-SC and Syn-Lin were regulated in a different way between women and men.…”
Section: Discussionsupporting
confidence: 63%
“…Interestingly, we observed a significant increase in all DSB repair mechanisms after the first 2 Gy dose and a recovery to steady state at D8. This confirmed that the DDR can be stimulated after a physical insult in PBMCs and PBMCs recovered from this damage in few days [ 31 ]. Age does not have any effect on the DNA repair profiles, whether NHEJ, Syn-SC and Syn-Lin were regulated in a different way between women and men.…”
Section: Discussionsupporting
confidence: 63%
“…It is worth noting that in physiological state, lymphocytes generate numerous DNA DSBs, which activate cellular DNA damage response (DDR). Interestingly, DDR capacity is different in various lymphocyte subsets being the strongest in NK cells, and the weakest in B lymphocytes, which correlates inversely with DNA damage-related survival ( 72 ). Recent studies have revealed that physiologic DNA SBs formation and DDR can initiate a genetic program that is unique and important for developing and maturation of lymphocytes.…”
Section: Discussionmentioning
confidence: 99%